2000
DOI: 10.1038/sj.ejcn.1601102
|View full text |Cite
|
Sign up to set email alerts
|

Associations of alpha-linolenic acid and linoleic acid with risk factors for coronary heart disease

Abstract: Background: Prevention of coronary heart disease (CHD) in high-risk subjects. Objective: To investigate the associations of dietary intake of alpha-linolenic acid (ALA) and linoleic acid (LA) as assessed by food frequency questionnaire and in the plasma cholesteryl ester (CE), with CHD risk factors. Design: Baseline data of a double-blind, randomized placebo-controlled trial. Subjects have hypercholesterolemia (6.0 ± 8.0 mmolal) and at least two other CHD risk factors (n 266). Results: The reported dietary ALA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 28 publications
0
24
0
2
Order By: Relevance
“…Consumption frequencies were reported per day, week or month. At baseline, Pearson's correlation coefficient of ALA intake as assessed by the questionnaire and the content of ALA in the cholesteryl ester was 0.37 (Po0.01) (Bemelmans et al, 2000). Hence, the questionnaire assesses intake of ALA reasonably well.…”
Section: Measurementsmentioning
confidence: 81%
“…Consumption frequencies were reported per day, week or month. At baseline, Pearson's correlation coefficient of ALA intake as assessed by the questionnaire and the content of ALA in the cholesteryl ester was 0.37 (Po0.01) (Bemelmans et al, 2000). Hence, the questionnaire assesses intake of ALA reasonably well.…”
Section: Measurementsmentioning
confidence: 81%
“…However, the rationale of replacing n-3 long-chain PUFA (LC-PUFA) by their precursor ALA is still under debate, especially concerning their respective efficiency and mechanisms of action [8]. Indeed, ALA and its long chain derivatives exhibit similar positive effects on etiologic factors of CVD such as hemostasis, thrombogenesis [9], and blood pressure [10]. In contrast, the effects of ALA on lipid metabolism are still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Results from these surveys have indicated that dietary ALA intake is not related (Bemelmans et al, 2000;Djousse et al, 2001;Djousse et al, 2003) or negatively associated (Salonen et al, 1987;Salonen et al, 1988;Djousse et al, 2005) with blood pressure levels. Others have used instead the content of ALA in plasma lipids or adipose tissue and, likewise, reported either an inverse association (Berry and Hirsch, 1986;Bemelmans et al, 2000) or no relationship (Riemersma et al, 1986;Simon et al, 1996;Grimsgaard et al, 1999). Another approach has been the supplementation of the diet with ALA and the prospective monitoring of blood pressure.…”
Section: Introductionmentioning
confidence: 99%